A near-infrared light-responsive upconversion nanocomposite material, its preparation method and application
By converting rare-earth nanoparticle cores and porphyrin metal-organic framework shells into composite materials, and utilizing heavy atom effects and triplet sensitization processes, the singlet oxygen yield and bactericidal effect of near-infrared photodynamic therapy were improved. This solved the problems of limited excitation depth and low yield of photosensitizers in existing technologies, and achieved highly efficient photodynamic therapy.
Patent Information
- Application Number
- CN202311420616.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2026-01-06
- Estimated Expiration
- 2043-10-30
AI Technical Summary
In existing photodynamic therapy, the ultraviolet or visible light excitation of photosensitizers leads to shallow penetration depth of biological tissues and large photodamage, and the low singlet oxygen yield of photosensitizers limits their application; the small near-infrared absorption cross section of rare earth upconversion nanoparticles results in low quantum yield, and the intersystem crossing efficiency of existing dye sensitization systems is low.
A near-infrared light-responsive upconversion nanocomposite material is designed, employing a rare-earth upconversion nanoparticle core, a porphyrin metal-organic framework shell, and a near-infrared dye. The near-infrared laser is absorbed by the metal ion-modified porous porphyrin MOF shell, realizing energy transfer to the rare-earth upconversion nanoparticles. Combined with the heavy atom effect and triplet sensitization process, the singlet oxygen production and photodynamic sterilization effect are improved.
It achieves high efficiency in singlet oxygen production and photodynamic sterilization, with a sterilization rate of 99.999%, and is suitable for photodynamic therapy of deep tissues.
Smart Images

Figure CN119909195B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanoluminescent materials technology, and particularly relates to a near-infrared light-responsive upconversion nanocomposite material, its preparation method and application. Background Technology
[0002] Traditional photosensitizers (PS) for photodynamic therapy (PDT) are often excited by ultraviolet or visible light. The wavelengths of ultraviolet or visible light not only have a shallow penetration depth into biological tissues, but also cause greater photodamage to biological tissues. At the same time, current photosensitizers have a relatively low reactive oxygen species yield, which limits their further application.
[0003] Rare-earth-doped upconversion nanoparticles (UCNPs) have distinguished themselves in upconversion nanosystems due to their excellent photostability, tunable luminescence properties, large anti-Stokes shift, and low biotoxicity. Near-infrared photodynamic therapy based on UCNPs has been extensively studied, with strategies such as physical adsorption, covalent conjugation, silica encapsulation, and heterostructure composites being employed to load PS onto UCNPs. Novel nanoporphyrin metal-organic frameworks (PMOFs) allow porphyrin photosensitizers to be periodically arranged within the MOF framework, thereby increasing the photosensitizer loading content, further preventing self-quenching caused by photosensitizer aggregation, and also addressing the water solubility issue. The UCNP / PMOF heterostructure achieves functional complementarity between the two. Due to the significant spectral overlap between the upconversion luminescence (UCL) of UCNPs and the absorption spectra of PMOFs, UCNPs can efficiently transfer energy to PMOFs, enabling PMOFs to respond to different near-infrared bands. Furthermore, the high porosity and large specific surface area of PMOFs allow for the adsorption of large amounts of O2 and the loading of various guest molecules, thus achieving higher singlet oxygen levels than pure PS molecules. 1 O2 generation efficiency. However, UCNPs have a small absorption cross-section for near-infrared light, resulting in a low quantum yield of upconversion to visible light; in addition, the problem of low singlet oxygen yield due to defects in the optical properties of the photosensitizer itself still exists.
[0004] Recent studies have found that near-infrared dyes with large absorption cross-sections can sensitize UCNPs through the antenna effect, thereby significantly improving the luminescence intensity of UCNPs. Furthermore, introducing heavy atom effects into dye-sensitized UCNP systems can promote spin-orbit coupling and intersystem crossing (ISC) processes in dye molecules, further enhancing the upconversion luminescence intensity of dye triplet-state sensitized UCNPs. However, existing dye-sensitized UCNP systems suffer from low ISC efficiency, limiting the more effective triplet-state sensitization process. Moreover, most photosensitizer molecules modified with heavy atoms are excited by ultraviolet or visible light, which is easily absorbed and scattered by biological tissues, resulting in limited penetration depth. Additionally, ultraviolet or visible light can easily damage biological tissues. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a near-infrared light-responsive upconversion nanocomposite material, its preparation method, and its application. The nanocomposite material exhibits excellent singlet oxygen production and photodynamic bactericidal effect.
[0006] In a first aspect, the present invention provides a near-infrared light-responsive upconversion nanocomposite material, the nanocomposite material comprising a rare earth upconversion nanoparticle core, a porphyrin metal-organic framework shell, a near-infrared dye loaded in the pores of the porphyrin metal-organic framework, and an amphiphilic phospholipid polymer modified on the outer surface of the porphyrin metal-organic framework, wherein the metal ion in the porphyrin metal-organic framework shell is a metal ion with a heavy atom effect, for example, at least one selected from Pt(II), Pd(II), Cu(II), Mn(II) or Ir(IV).
[0007] According to an embodiment of the present invention, near-infrared dye molecules loaded in a porous porphyrin MOF shell modified with metal ions such as Pt(II), Pd(II), Cu(II), Mn(II), or Ir(IV) absorb near-infrared laser light and then transfer the energy to rare-earth upconversion nanoparticles to achieve efficient upconversion visible light emission. The photosensitizer porphyrin molecules absorb the visible light from the rare-earth upconversion nanoparticles to generate singlet oxygen. The metal ions in the composite material have a heavy atom effect, and the triplet sensitization luminescence of UCNPs by the near-infrared dye and the singlet oxygen generation ability of the porphyrin photosensitizer are simultaneously enhanced. Therefore, the composite material exhibits excellent singlet oxygen production and photodynamic bactericidal effect.
[0008] According to an embodiment of the present invention, the rare earth upconversion nanoparticles are upconversion nanoparticles doped with rare earth ions. Preferably, the rare earth upconversion nanoparticles are selected from at least one of NaYF4:Yb,Er, NaLuF4:Yb,Er, or NaGdF4:Yb,Er, for example, upconversion nanoparticles NaGdF4:Yb,Er doped with Yb and Er ions. The NaGdF4:Yb,Er can achieve Yb upconversion under 980nm laser pumping. 3+ Sensitization Er 3+ Upconversion luminescence.
[0009] According to an embodiment of the present invention, the porphyrin metal-organic framework is selected from at least one of PCN-224(Pt), PCN-222(Pt), PCN-223(Pt), PCN-224(Pd), PCN-222(Pd), PCN-223(Pd), PCN-224(Cu), PCN-222(Cu), PCN-223(Cu), PCN-224(Mn), PCN-222(Mn), PCN-223(Mn), PCN-224(Ir), PCN-222(Ir), and PCN-223(Ir), for example, PCN-224(Pt), with a platinum(II)-tetra(4-carboxyphenyl)porphyrin photosensitizer (Pt-TCPP) modified with the heavy atom Pt in PCN-224(Pt) as a ligand.
[0010] According to an embodiment of the present invention, the metal ions Pt(II), Pd(II), Cu(II), Mn(II), and Ir(IV) have an external heavy atom effect, and more excitons are transferred from S1 to T1 through the ISC process, which shortens the effective lifetime of the near-infrared dye, improves the ISC efficiency of the near-infrared dye, and thus promotes the near-infrared dye sensitization process.
[0011] According to an embodiment of the present invention, the near-infrared dye is a cyanine dye that absorbs near-infrared light, preferably selected from at least one of IR820, IR806, IR825 or IR808; exemplaryly, the near-infrared dye may be IR808.
[0012] According to an embodiment of the present invention, the amphiphilic phospholipid polymer is selected from at least one of DSPE-mPEG (distearyl phosphatidylethanolamine-polyethylene glycol), DSPE-PEG-NH2 (distearyl phosphatidylethanolamine-polyethylene glycol-amino crosslinker), and DSPE-PEG-COOH (distearyl phosphatidylethanolamine-polyethylene glycol carboxyl group); exemplaryly, the amphiphilic phospholipid polymer may be DSPE-PEG-NH2-2000.
[0013] As an example, the upconversion nanocomposite material comprises a rare earth upconversion nanoparticle core of NaGdF4:Yb,Er and a porphyrin metal-organic framework (PCN-224(Pt)) shell. The porphyrin metal-organic framework (PCN-224(Pt)) contains a near-infrared dye IR808 distributed in its pores. The outer surface of the porphyrin metal-organic framework (PCN-224(Pt)) is modified with an amphiphilic phospholipid polymer DSPE-PEG-NH2-2000. The upconversion nanocomposite material is denoted as UMOF(Pt) / IR808-Lipo, and the composite material not modified with DSPE-PEG-NH2-2000 is denoted as UMOF(Pt) / IR808.
[0014] According to an embodiment of the present invention, the NaGdF4:Yb,Er core is hexagonal, for example, a highly crystalline hexagonal phase.
[0015] According to an embodiment of the present invention, the UMOF(Pt) / IR808 is a spherical nanoparticle with a size of 32-34 nm.
[0016] According to embodiments of the present invention, the UMOF(Pt) / IR808 and UMOF(Pt) / IR808-Lipo have essentially the following properties: Figure 3 The image shown is a scanning transmission electron microscope image.
[0017] According to an embodiment of the present invention, the UMOF(Pt) / IR808 nanoparticles have essentially the following properties: Figure 4 The X-ray diffraction pattern shown.
[0018] According to an embodiment of the present invention, the UMOF(Pt) / IR808 has essentially the following characteristics: Figure 5 The diagram shows a cascaded energy transfer process.
[0019] According to an embodiment of the present invention, NaGdF4:Yb,Er exhibits characteristic upconversion luminescence, which has strong spectral overlap with the Q-band absorption of porphyrin PCN-224(Pt) near 526 and 545 nm, and the energy transfer from the NaGdF4:Yb,Er core to the porphyrin MOF shell of the UMOF(Pt) / IR808 is efficient.
[0020] According to an embodiment of the present invention, the UMOF(Pt) / IR808 has essentially the following characteristics: Figure 7 The UCL spectrum shown.
[0021] According to an embodiment of the present invention, the average FRET efficiency of the UMOF(Pt) / IR808 is approximately 48.5%.
[0022] According to an embodiment of the present invention, the UMOF(Pt) / IR808 has essentially the following characteristics: Figure 9 The PL attenuation diagram is shown.
[0023] According to an embodiment of the present invention, the effective surface lifetime of IR808 in the UMOF(Pt) / IR808 is 141 ps.
[0024] According to an embodiment of the present invention, the ISC efficiency of IR808 in the UMOF(Pt) / IR808 is 73.9%.
[0025] According to an embodiment of the present invention, the UMOF(Pt) / IR808 exhibits the following characteristics under 808nm near-infrared light irradiation: Figure 10 of 1 O2 generation capability.
[0026] According to an embodiment of the present invention, the UMOF(Pt) / IR808-Lipo exhibits essentially the following properties under 808nm near-infrared light irradiation. Figure 11 The test results demonstrate the superior bactericidal ability of methicillin-resistant Staphylococcus aureus (MRSA), with an antibacterial efficiency of 5.27 log. 10 (>99.999%).
[0027] Secondly, the present invention also provides a method for preparing the above-mentioned upconversion nanocomposite material, the method comprising the following steps:
[0028] (1) Preparation of rare earth upconversion nanoparticles;
[0029] (2) A porphyrin metal-organic framework shell is grown on the surface of the rare earth upconversion nanoparticles in step (1) to obtain the core-shell structured nanocomposite material UMOF(X);
[0030] (3) Loading near-infrared dyes onto the core-shell structured nanocomposite material of step (2);
[0031] (4) The surface of the composite material with near-infrared dye obtained in step (3) is modified with an amphiphilic phospholipid polymer to prepare the upconversion nanocomposite material UMOF(X) / YLipo.
[0032] According to an embodiment of the present invention, step (2) includes the following steps: using a small molecule assisted ligand incorporation method, a porphyrin metal-organic framework shell is grown in situ on the surface of the rare earth onconversion nanoparticles in step (1).
[0033] According to an embodiment of the present invention, the rare earth upconversion nanoparticles, porphyrin metal-organic framework shell, and near-infrared dye have the definitions described above.
[0034] According to an embodiment of the present invention, X is a metal ion selected from at least one of Pt(II), Pd(II), Cu(II), Mn(II) or Ir(IV).
[0035] According to an embodiment of the present invention, Y is a near-infrared dye.
[0036] According to an embodiment of the present invention, step (2) includes the following steps:
[0037] a. DHCA-UCNPs were obtained by reacting rare earth upconversion nanoparticles with 3,4-dihydroxyphenylpropionic acid.
[0038] b. DHCA-UCNPs, X-TCPP, ZrOCl2·8H2O and benzoic acid were reacted in solution to obtain the core-shell structured nanocomposite material UMOF(X).
[0039] According to an embodiment of the present invention, step a includes the following steps: introducing rare earth upconversion nanoparticles into a solution of N,N-dimethylformamide containing nitrosotetrafluoroborate and stirring vigorously, collecting NOBF4-UCNPs by centrifugation, and further adding 3,4-dihydroxyphenylpropionic acid into the solution containing NOBF4-UCNPs and stirring overnight, and centrifuging to obtain DHCA-UCNPs.
[0040] According to an embodiment of the present invention, the molar ratio of the rare earth upconversion nanoparticles to nitrosotetrafluoroborate is 1:(1-2), for example, 1:1.2.
[0041] According to an embodiment of the present invention, the molar ratio of NOBF4-UCNPs to 3,4-dihydroxyphenylpropionic acid is 1:(1-3), for example, 1:1.6.
[0042] According to an embodiment of the present invention, step b includes the following steps: dissolving DHCA-UCNPs in a solution containing ZrOCl2·8H2O, adding X-TCPP solution and benzoic acid solution, and reacting at a temperature of 90-120℃ for 5-10 h to obtain a core-shell structured nanocomposite material UMOF(X).
[0043] According to an embodiment of the present invention, the molar ratio of DHCA-UCNPs, X-TCPP, ZrOCl2·8H2O and benzoic acid is 1:(0.1~2):(0.5~1.2):(25~30), for example, 1:0.12:0.9:27.
[0044] According to an embodiment of the present invention, step (3) includes the following steps: loading near-infrared dyes onto the core-shell structured nanocomposite material of step (2) by a solvent-assisted method.
[0045] According to an embodiment of the present invention, the dried core-shell nanocomposite material UMOF(X) is dispersed in a near-infrared dye Y solution with a concentration of 1.2 mmol / L and stirred overnight to obtain a core-shell nanocomposite material loaded with near-infrared dye.
[0046] According to an embodiment of the present invention, the stirring rate is 300 to 900 rpm / min, for example, 600 rpm / min.
[0047] According to an embodiment of the present invention, after stirring overnight, the following steps are further included: centrifuging and washing with DMF, collecting the substrate, and obtaining a core-shell structured nanocomposite material UMOF(X) / Y loaded with near-infrared dye.
[0048] According to an embodiment of the present invention, the near-infrared dye Y solution is a DMF solution of near-infrared dye Y.
[0049] According to an embodiment of the present invention, step (4) includes the following steps: dispersing UMOF(X) / Y in a solvent, adding an amphiphilic phospholipid polymer, stirring overnight in a dark environment at room temperature, and removing the solvent to obtain the upconversion nanocomposite material UMOF(X) / Y-Lipo.
[0050] According to an embodiment of the present invention, the molar ratio of UMOF(X) / Y to the amphiphilic phospholipid polymer is 1:(0.2-0.8), 1:0.4.
[0051] According to an embodiment of the present invention, solvent removal includes the following steps: removing the solvent from the reaction product by rotary evaporation at a temperature of 30–60°C.
[0052] According to an embodiment of the present invention, after removing the solvent, the following steps are further included: washing the collected solid with ultrapure water multiple times to obtain the upconversion nanocomposite material UMOF(X) / Y-Lipo.
[0053] According to an embodiment of the present invention, the solvent is selected from chloroform, acetonitrile, ethanol, for example, chloroform.
[0054] Thirdly, the present invention also provides an application of the upconversion nanocomposite material described above in photodynamic therapy.
[0055] Beneficial effects
[0056] 1) This invention designs and synthesizes a near-infrared light-responsive upconversion nanocomposite material. By integrating UCNPs, heavy atom-modified PMOFs, and a near-infrared dye into a core-shell structure, the PMOF shell can not only act as a photosensitizer to absorb the upconversion luminescence (UCL) of UCNPs to generate singlet oxygen (…). 1O2 can also be used as a porous host material to load near-infrared dyes. By utilizing the triplet sensitization of UCNPs by near-infrared dyes and the heavy atom effect of heavy atoms, an efficient energy cascade transfer process can be constructed, ultimately achieving a significant improvement in singlet oxygen yield and in vitro antibacterial efficiency, which can be used for efficient PDT (photodynamic therapy) antibacterial.
[0057] 2) The nanocomposite material synthesized in this invention includes a rare earth upconversion nanoparticle core, a porphyrin metal-organic framework shell, a near-infrared dye loaded in the pores of the porphyrin metal-organic framework, and an amphiphilic phospholipid polymer modified on the outer surface of the porphyrin metal-organic framework. The metal ion in the porphyrin metal-organic framework shell is at least one of the heavy atoms Pt(II), Pd(II), Cu(II), Mn(II), or Ir(IV). The near-infrared dye molecules loaded in the porous porphyrin MOF shell modified with metal ions absorb near-infrared laser light and then transfer the energy to the rare earth upconversion nanoparticles to achieve efficient upconversion visible light emission.
[0058] The rare-earth upconversion nanoparticles in this invention exhibit characteristic upconversion luminescence, which strongly overlaps with the Q-band absorption of porous porphyrin MOF shells near 526 and 545 nm. Furthermore, the rare-earth ions in the composite material, such as Er... 3+ The UCL lifetime is significantly shortened in the characteristic wavelength band. Therefore, the energy transfer from the rare-earth upconversion nanoparticle core to the porphyrin MOF shell in this composite material is effective, with an average FRET efficiency of 48.5%. The metal ions in the composite material exhibit a heavy atom effect, simultaneously enhancing the triplet-state sensitization luminescence of UCNPs by the near-infrared dye and the singlet oxygen generation ability of the porphyrin photosensitizer. Compared to free near-infrared dyes, the nanocomposite material in this invention shows a significantly reduced stress intensity under near-infrared light, such as 825 nm excitation light, and a shortened PL decay lifetime. The overall energy transfer efficiency from the near-infrared dye to UCNPs is effectively increased to, for example, 49.9%, indicating that the external heavy atom effect of metal ions can accelerate the S1 to T1 ISC process in the near-infrared dye, thereby improving the energy transfer efficiency of the dye triplet-state sensitized UCNPs. The porphyrin photosensitizer molecule can absorb visible light from the rare-earth upconversion nanoparticles to generate singlet oxygen. 1 The O2 yield is 2.8 times that of UMOF, and when used for the sterilization of methicillin-resistant Staphylococcus aureus, it is significantly higher with low-power lasers, such as an 808nm laser (0.4W / cm²). 2 Under these conditions, the sterilization rate is better than 99.999%, and the antibacterial effect reaches 5.27 log. 10 Therefore, the composite material exhibits excellent singlet oxygen production and photodynamic bactericidal effect.
[0059] 3) The nanocomposite material of the present invention is very suitable as a photodynamic therapy platform, providing a new approach for the development of deep tissue, efficient and low-toxicity photodynamic therapy. Attached Figure Description
[0060] Figure 1 This is a schematic diagram of the design and structure of the upconversion nanocomposite material UMOF(Pt) / IR808, which combines heavy atom effect and dye-sensitized rare earth luminescence, for use in antibacterial PDT under 808nm near-infrared light irradiation.
[0061] Figure 2 This is a schematic diagram of the synthesis process of UMOF(Pt) / IR808 in Example 1 of the present invention.
[0062] Figure 3 Transmission electron microscopy (TEM) images of UCNPs, UMOF(Pt), and UMOF(Pt) / IR808 nanoparticles prepared in Example 1 of this invention.
[0063] Figure 4 The image shows the X-ray diffraction pattern of the UMOF(Pt) / IR808 nanoparticles prepared in Example 1 of this invention.
[0064] Figure 5 This is a schematic diagram of the cascaded energy transfer from IR808 to UCNPs and then to PMOFs in Embodiment 2 of the present invention.
[0065] Figure 6 a represents the UCL spectrum of UCNPs and the UV-Vis absorption spectrum of PCN-224(Pt) in Example 2 of this invention.
[0066] Figure 6 b represents the UCL spectra of DHCA-UCNPs and UMOF(Pt) under 980nm excitation in Example 2 of this invention.
[0067] Figure 7 The UCL attenuation curves of DHCA-UCNPs, UMOF(Pt) and UMOF(Pt) / IR808 emitted at 521 and 540 nm in Embodiment 2 of the present invention are shown.
[0068] Figure 8 The kinetic curves of free IR808, NaGdF4@IR808, NaGdF4@MOF / IR808 and NaGdF4@MOF(Pt) / IR808 in Example 2 of this invention are detected at the SE center (825nm).
[0069] Figure 9This refers to the PL attenuation of free IR808 and IR808 in UMOF / IR808 and UMOF(Pt) / IR808 in Embodiment 2 of the present invention.
[0070] Figure 10 This refers to the singlet oxygen production capacity of UMOF(Pt) / IR808 in Example 3 of the present invention, measured using DPBF, SOSG, and ESR methods respectively.
[0071] Figure 11 This is a comparison chart of the antibacterial effects of UMOF(Pt)-Lipo, IR808, UMOF / IR808-Lipo, and UMOF(Pt) / IR808-Lipo on MRSA under 808nm or 980nm laser irradiation in Example 4 of the present invention.
[0072] Figure 12 These are photographs of MRSA colonies at different dilutions (c / %) on LB agar plates in Example 4 of this invention, treated with different agents. Detailed Implementation
[0073] The following will provide a more detailed description of the materials, preparation methods, and applications of the present invention with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0074] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0075] Instruments and equipment:
[0076] The polycrystalline X-ray diffractometer used for powder diffraction characterization of the product in this embodiment of the invention is a MiniFlex2, manufactured by Rigaku, with a copper target radiation wavelength of λ = 0.154187 nm.
[0077] The transmission electron microscope (TEM) used for the product inspection in this embodiment of the invention is a TECNAI G. 2 F20, manufactured by FEI.
[0078] The UV-Vis spectrophotometer used for UV-Vis absorption spectroscopy characterization of the product in this embodiment of the invention is a Lambda365 manufactured by Perkin-Elmer.
[0079] The electron spin resonance (ESR) spectrometer used for characterizing the product in this embodiment of the invention is model E500 10 / 12, manufactured by Bruker Biospin GMBH.
[0080] The multi-functional microplate reader used for absorbance testing of the product in this embodiment of the invention is a Synergy4, manufactured by BioTek.
[0081] The steady-state transient fluorescence spectrometer used for fluorescence emission spectroscopy and fluorescence lifetime characterization of the product in this embodiment of the invention is a model FLS980 manufactured by Edinburgh, and the excitation source is a xenon lamp and a 390nm LD pulsed laser.
[0082] The fluorescence spectrometer used for upconversion fluorescence emission spectroscopy characterization of the product in this embodiment of the invention is a model FLS920 manufactured by Edinburgh, and the excitation source is a 980nm and 808nm semiconductor laser.
[0083] The steady-state transient fluorescence spectrometer used for upconversion fluorescence emission spectroscopy and fluorescence lifetime characterization of the product in this embodiment of the invention is a model FSP920C manufactured by Edinburgh, and the excitation source is an OPO pulsed laser of 400-2500nm.
[0084] Example 1: See Figure 2 As shown, the preparation method of the near-infrared light-responsive nanophotodynamic therapy platform UMOF(Pt) / IR808-Lipo includes the following steps:
[0085] (1) Upconversion nanoparticles NaGdF4:18%Yb,2%Er were prepared by solid-liquid thermal decomposition method.
[0086] Weigh rare earth acetates Gd(CH3COO)3·4H2O (0.8 mmol), Yb(CH3COO)3·4H2O (0.18 mmol) and Er(CH3COO)3·4H2O (0.02 mmol), place them in a two-necked flask, add oleic acid (8 mL) and octadecene (12 mL) and stir to mix. The mixture was then heated to 180°C under a nitrogen atmosphere with stirring, held at that temperature for 20 min, and then cooled to room temperature to obtain a mixed solution. Sodium hydrogen fluoride (NaHF2) (2 mmol) was then weighed and added to the mixed solution. Under nitrogen protection, the solution was heated to 250°C and stirred vigorously for 30 min. The temperature was then rapidly increased to 310°C and maintained at that temperature for 30 min. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. Ethanol was added to a two-necked flask to precipitate the product, and the precipitate was collected by centrifugation. The precipitate was washed multiple times with cyclohexane and ethanol. The final product was NaGdF4:18%Yb,2%Er rare earth upconversion nanoparticles (UMOF).
[0087] (2) Preparation of core-shell UMOF(Pt) composite material by small molecule auxiliary ligand incorporation method: 0.18 mmol NaGdF4:18% Yb,2% Er obtained in step (1) was added to 2 mL of dimethylformamide (DMF) solution containing 25 mg tetrafluoroboric acid (NOBF4). After stirring vigorously for 30 min, NOBF4-UCNPs were collected by centrifugation. 100 mg of 3,4-dihydroxyphenylpropionic acid (DHCA) was added to 4 mL of DMF solution containing 0.18 mmol NOBF4-UCNPs (under normal temperature and air conditions) and stirred overnight. Finally, DHCA-UCNPs were collected by centrifugation.
[0088] Solution A was prepared by adding 3.0 mg ZrOCl2·8H2O to 4 mL of a mixed solvent containing DMF and ethanol in a 1:1 volume ratio; solution B was prepared by adding 1.2 mg Pt-TCPP to 4 mL of a mixed solvent containing DMF and ethanol in a 1:1 volume ratio; and solution C was prepared by adding 28 mg benzoic acid to 4 mL of a mixed solvent containing DMF and ethanol in a 1:1 volume ratio.
[0089] Solution A, solution B, and solution C were each sonicated for 5 minutes. 0.18 mmol DHCA-UCNPs were added to solution A and stirred for 15 minutes to obtain reaction solution A. Then, solution B and solution C were added to reaction solution A. The mixture was then heated in an oil bath at 100°C for 7 hours, cooled to room temperature, and collected by centrifugation to obtain the core-shell composite material UMOF(Pt).
[0090] (3) The near-infrared dye IR808 was loaded onto the UMOF(Pt) prepared in step (2) by solvent-assisted ligand incorporation method to obtain the composite material UMOF(Pt) / IR808: First, the synthesized UMOF(Pt) sample was washed twice by centrifugation with DMF and acetone. The washed sample was placed in a vacuum drying oven (60℃, overnight). The dried 0.18 mmol sample was dispersed again in DMF solution with IR808 concentration of 1.2 mmol / L and stirred overnight in the dark (600 rpm / min). Finally, it was washed twice by centrifugation with DMF and the substrate and the supernatant of the first centrifugation were collected. The obtained substrate is the target product UMOF(Pt) / IR808.
[0091] (4) UMOF(Pt) / IR808-Lipo was prepared by modifying the UMOF(Pt) / IR808 obtained in step (3) with the amphiphilic phospholipid polymer DSPE-PEG-NH2-2000.
[0092] First, 0.18 mmol of UMOF(Pt) / IR808 was ultrasonically dispersed in 5 mL of chloroform (CHCl3), and then 10 mg of the amphiphilic phospholipid polymer DSPE-PEG-NH2-2000 was added. The mixture was stirred overnight in the dark at room temperature. The next day, the solvent was removed by rotary evaporation at 40 °C. The solid UMOF(Pt) / IR808-Lipo was collected by repeatedly rinsing with ultrapure water. Finally, the precipitate was centrifuged and redispersed in 4 mL of ultrapure water for later use.
[0093] The preparation methods for other control group products UMOF, UMOF(Pt), and UMOF / IR808 are similar to those described above.
[0094] UMOF represents a material without Pt modification and without IR808 loading, that is, the product prepared in the same way as steps (1) to (2) except that Pt-TCPP in step (2) is replaced with H2TCPP.
[0095] UMOF(Pt) indicates that the material is not loaded with IR808, i.e., the product prepared in steps (1) to (2).
[0096] UMOF / IR808 indicates a material without Pt modification, that is, a product prepared in the same way as steps (1) to (3) except that Pt-TCPP in step (2) is replaced with H2TCPP.
[0097] Appendix Figure 3a, b, and c are transmission electron microscopy (TEM) images of NaGdF4:Yb,Er nanocrystals (UMOF), UMOF(Pt), and UMOF(Pt) / IR808, respectively. The TEM images show that the NaGdF4:Yb,Er nanocrystals synthesized via solid-liquid thermal decomposition have hexagonal cores and exhibit good dispersion and uniform size distribution. The TEM images of UMOF(Pt) and UMOF(Pt) / IR808 clearly show core-shell nanoparticles with UCNP cores and MOF shells.
[0098] See Figure 4 As shown, the powder X-ray diffraction (PXRD) pattern reveals typical diffraction peaks in UMOF(Pt) corresponding to the cubic phase of PCN-224 and the highly crystalline hexagonal phase of β-NaGdF4:18%Yb,2%Er, confirming that the two heterostructures possess high phase purity and high crystallinity.
[0099] Example 2: Optical properties of prepared NaGdF4:Yb,Er,UMOF(Pt),UMOF(Pt) / IR808 and Pt heavy atom effect enhancing dye triplet sensitized UCNPs
[0100] This embodiment tests the NaGdF4:Yb,Er,UMOF(Pt),UMOF(Pt) / IR808 prepared in Example 1 to further verify the excellent optical properties of this upconversion nanocomposite material.
[0101] Appendix Figure 5 The process of multi-step cascaded energy transfer from IR808 to UCNPs at the core and then to Pt-TCPP ligands in the MOF shell was demonstrated. Under 980 nm laser excitation, NaGdF4:Yb,Er exhibited characteristic upconversion luminescence (UCL) at 654 nm, 540 nm and 521 nm, which strongly overlapped with the Q-band absorption of porphyrin PCN-224(Pt) near 526 nm and 545 nm.
[0102] Simultaneously, it was observed that under near-infrared light excitation at 980 nm, the upconversion emission of UMOF(Pt) decreased significantly compared to DHCA-UCNPs, especially at 521 nm and 540 nm (see appendix). Figure 6 This indicates that the energy transfer from the UCNP core to the porphyrin MOF shell is efficient.
[0103] Appendix Figure 7 Er in UCNPs (corresponding to DHCA-UCNPs in the figure), UMOF(Pt), and UMOF(Pt) / IR808 samples was investigated. 3+ At 521nm ( Figure 7 a) and 540nm ( Figure 7 The UCL lifetime at point a) can be seen from the figure. At 521 nm and 540 nm, the lifetimes of UCNPs to UMOF(Pt) or UMOF(Pt) / IR808 are significantly shortened, indicating that the fluorescence resonance energy transfer (FRET) process from UCNPs to PCN-224(Pt) is effective. The average FRET efficiency of UMOF(Pt) / IR808 is calculated to be approximately 48.5%.
[0104] This invention employs femtosecond transient absorption (fs-TA) spectroscopy and transient PL spectroscopy to analyze the triplet energy transfer (TET) from IR808 to UCNPs. The singlet lifetime of the dye is mainly affected by the intersystem crossing probability and the radiative transition probability. By comparing the changes in the stimulated emission rate of the same dye loaded with different nanocrystals, the differences in intersystem crossing efficiency can be determined. Due to the external heavy atom effect of Pt(II), more excitons transfer from S1 to T1 through the ISC process, which is a key factor promoting the dye sensitization process.
[0105] To study the effect of nanocrystals on dyes, in this embodiment, following step (3) in Example 1, NaGdF4@MOF(Pt) was replaced with NaGdF4 and NaGdF4@MOF in sequence to prepare NaGdF4@IR808 and NaGdF4@MOF / IR808. The kinetic curves of IR808, NaGdF4@IR808, NaGdF4@MOF / IR808, and NaGdF4@MOF(Pt) / IR808 at the SE center (825nm) were detected respectively.
[0106] See Figure 8 As shown, compared with free IR808, the effective surface lifetime of IR808 in the NaGdF4@MOF(Pt) / IR808 composite material was shortened from 542 ps to 141 ps. Accordingly, the ISC efficiency of IR808 in the NaGdF4@MOF(Pt) / IR808 composite material reached 73.9%. In contrast, the recovery time of IR808 in Pt(II)-free NaGdF4@IR808 and its counterparts in NaGdF4@MOF / IR808 did not change significantly compared with free dye, with effective lifetimes of 503 ps and 478 ps, respectively, which are similar to those of free IR808.
[0107] See Figure 9As shown, compared with free IR808, the fluorescence intensity of UMOF(Pt) / IR808 at 825 nm is significantly reduced, the PL decay lifetime is shortened from 794 ps to 398 ps, and the overall energy transfer efficiency from IR808 to UCNPs is increased to 49.9%. These results are consistent with the results of fs-TA spectroscopy, indicating that the external heavy atom effect of Pt(II) can accelerate the ISC process from S1 to T1 in IR808, thereby improving the energy transfer efficiency of dye triplet sensitized UCNPs.
[0108] Example 3: UMOF(Pt) / IR808, as a near-infrared responsive photosensitizer, exhibits excellent singlet oxygen production. To evaluate the singlet oxygen production capacity of UMOF(Pt) / IR808, we selected 1,3-diphenylisobenzofuran (DPBF), 4-amino-2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMP), and SOSG (Singlet Oxygen SensorGreen) as singlet oxygen detection probes. The specific implementation steps are as follows:
[0109] (1) Using 1,3-diphenylisobenzofuran as a probe molecule, the sample production was determined by detecting changes in DPBF absorbance. 1 Specifically, to assess the O2 capacity, 0.2 mL of a sample solution containing a mixture of UMOF(Pt) / IR808 and acetonitrile was added to a 96-well plate. The sample solution concentration was 1.5 mg / mL. Then, 2 μL of DPBF was added, with a control consisting of 2 μL of DPBF and 0.2 mL of acetonitrile without UMOF(Pt) / IR808. A power density of 0.5 W / cm² was used. 2 The solution was continuously irradiated for 8 min with a 980 nm or 808 nm laser (ConnetFiber Optics, China). The absorbance of DPBF at 407 nm was recorded on a multi-functional microplate reader (Synergy 4, BioTek) at 0, 1, 2, 3, 4, 6, and 8 min.
[0110] Furthermore, control group samples (such as UMOF, UMOF / IR808, and UMOF(Pt)) were set up and tested using the same testing method.
[0111] (2) Using singlet oxygen green fluorescent probe (SOSG) as the probe molecule, the generation of oxygen in the sample is detected by detecting changes in SOSG fluorescence intensity. 1The O2 capability was tested by adding 6 μL of SOSG probe to 2 mL of acetonitrile solution containing UMOF(Pt) / IR808. The concentration of UMOF(Pt) / IR808 in the acetonitrile solution was 0.2 mg / mL. Then, the probe was tested at 808 nm (0.5 W / cm). 2 Irradiate the solution with a laser or place it in the dark to avoid light. Monitor the real-time fluorescence intensity (Ex = 485 nm) of the solution every 2 minutes on an FLS 980 spectrometer. At the same time, set up control group samples (such as UMOF, UMOF / IR808, and UMOF(Pt)) and test the control group samples using the same test method.
[0112] (3) Using 2,2,6,6-tetramethylpiperidine (TMEP) as a trapping agent, electron spin resonance (ESR) spectra were measured to detect the ability of UMOF(Pt) / IR808 to generate singlet oxygen. 100 μL of UMOF(Pt) / IR808 ethanol solution was added to a 96-well plate, containing 0.2 mg / mL of UMOF(Pt) / IR808. Then, 20 μL of TEMP ethanol solution was added to each well, and the plate was heated to 808 nm (0.5 W / cm²). 2 After irradiation with a laser for 10 minutes, the sample was aspirated using a capillary tube and subjected to paramagnetic resonance spectroscopy on a Hitachi JES-FA200 spectrometer. Simultaneously, control samples (such as UMOF, UMOF / IR808, and UMOF(Pt)) were set up and tested using the same method.
[0113] The results, obtained using DPBF, SOSG singlet oxygen probes, and ESR spectroscopy, are shown in the attached figure. Figure 10 As shown, UMOF(Pt) / IR808 exhibits high singlet oxygen production under 808 nm light excitation. 1 O2 yield comparison: UMOF(Pt) / IR808 > UMOF / IR808 > UMOF(Pt) > UMOF, where UMOF(Pt) / IR808... 1 The O2 yield was 2.8 times that of the control group (UMOF).
[0114] Example 4: UMOF(Pt) / IR808-Lipo, as a near-infrared light-responsive nanophotodynamic therapy platform, exhibits excellent photodynamic bactericidal effects.
[0115] This implementation case demonstrates the application of UMOF(Pt) / IR808-Lipo as a photodynamic therapy drug for in vitro photodynamic sterilization using the dilution-coating plate method. The specific implementation steps are as follows:
[0116] The activated methicillin-resistant Staphylococcus aureus (MRSA) was diluted with physiological saline and added to different wells of a 24-well plate, with a final bacterial concentration of 10⁻⁶ in each well. 6 CFU / mL, then UMOF(Pt) / IR808-Lipo and control samples UMOF(Pt)-Lipo and UMOF / IR808-Lipo were added to the bacterial culture in the wells. The concentrations of UMOF(Pt) / IR808-Lipo, UMOF(Pt)-Lipo, and UMOF / IR808-Lipo in the bacterial culture were all 0.1 mmol / L. The 24-well plate was placed in a 37°C incubator and incubated in the dark for 10 min, followed by irradiation with an 808 nm laser (0.35 W / cm²). 2 The bacterial solutions in different wells were irradiated for 10 min, with UMOF(Pt)-Lipo being irradiated for 10 min using a 980nm fiber laser at the same power density.
[0117] The MRSA bacterial solutions in different wells were diluted with physiological saline. The concentration gradient of the diluted solutions should be within the expected range (10). -1 CFU / mL, 10 -2 CFU / mL, 10 -3 CFU / mL, 10 -4 CFU / mL, 10 -5 The MRSA bacterial suspensions at different concentrations (CFU / mL) were plated. 100 μL of bacterial suspension was evenly spread on LB agar solid medium plates (each sample was plated 3 times). The plated medium plates were then inverted and incubated overnight at 37°C. The number of MRSA colonies in each medium plate was counted and recorded the next day. Each experiment was repeated three times.
[0118] From the appendix Figure 11 and 12 It can be seen that using an 808nm laser (0.4W / cm²) 2 Irradiation of a bacterial mixture with UMOF(Pt) / IR808-Lipo (800 μg / mL) for 10 min resulted in a bactericidal rate better than 99.999% and an inhibitory effect of 5.27 log₂O₅. 10 In contrast, the antibacterial effect of UMOF(Pt)-Lipo under 980nm irradiation is only 1.25 log. 10 The antibacterial efficacy of UMOF / IR808-Lipo was 2.49 log. 10Therefore, under the same conditions, the bactericidal effect of UMOF(Pt) / IR808-Lipo is significantly better than that of UMOF(Pt)-Lipo without IR808 modification and UMOF / IR808-Lipo without heavy atom Pt modification. The antibacterial experimental results are consistent with the previously measured singlet oxygen yield results, and verify the sensitizing effect of IR808 loading on UMOF(Pt) and the heavy atom effect of Pt. In summary, the above results indicate that UMOF(Pt) / IR808-Lipo can achieve highly efficient sterilization of MRSA under low-power near-infrared light triggering, and can serve as an excellent near-infrared triggered photodynamic sterilization nanoplatform.
[0119] The specific embodiments of the present invention have been described above by way of example. However, the scope of protection of the present invention is not limited to the above exemplary embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A near-infrared light responsive upconversion nanocomposite, characterized in that, The nanocomposite comprises a rare earth upconversion nanoparticle core, a porphyrin metal-organic framework shell, a near-infrared dye loaded in the porphyrin metal-organic framework pores, and an amphiphilic phospholipid polymer modified on the outer surface of the porphyrin metal-organic framework, wherein the metal ion in the porphyrin metal-organic framework shell is a metal ion having a heavy atom effect; The metal ion is selected from Pt(II); The rare earth upconversion nanoparticle is NaGdF4:Yb,Er; The porphyrin metal-organic framework is PCN-224(Pt); The near-infrared dye is IR808; The amphiphilic phospholipid polymer is selected from at least one of DSPE-mPEG, DSPE-PEG-NH2, and DSPE-PEG-COOH.
2. The near-infrared light responsive upconverting nanocomposite of claim 1, wherein, The upconversion nanocomposite comprises a rare earth upconversion nanoparticle NaGdF4:Yb,Er core, a porphyrin metal-organic framework PCN-224(Pt) shell, wherein the pores of the porphyrin metal-organic framework PCN-224(Pt) are distributed with a near-infrared dye IR808, and the outer surface of the porphyrin metal-organic framework PCN-224(Pt) is modified with an amphiphilic phospholipid polymer DSPE-PEG2000-NH2. The upconversion nanocomposite is denoted as UMOF(Pt) / IR808-Lipo, and the composite material not modified with DSPE-PEG2000-NH2 is denoted as UMOF(Pt) / IR808.
3. The near-infrared light responsive upconverting nanocomposite of claim 2, wherein, The average fluorescence resonance energy transfer efficiency of the UMOF(Pt) / IR808 is 48.5%; The surface effective lifetime of IR808 in the UMOF(Pt) / IR808 is 141 ps; The intersystem crossing efficiency of IR808 in the UMOF(Pt) / IR808 is 73.9%.
4. A method of preparing the up-conversion nanocomposite of any one of claims 2-3, wherein, The preparation method comprises the following steps: (1) preparing a rare earth upconversion nanoparticle; (2) growing a porphyrin metal-organic framework shell on the surface of the rare earth upconversion nanoparticle of step (1) to obtain a core-shell structure nanocomposite UMOF(X); (3) loading a near-infrared dye on the core-shell structure nanocomposite of step (2); (4) modifying an amphiphilic phospholipid polymer on the surface of the composite material with the near-infrared dye prepared in step (3) to obtain an upconversion nanocomposite UMOF(X) / Y-Lipo; wherein X is Pt(II) and Y is a near-infrared dye IR808.
5. The preparation method according to claim 4, characterized in that, Step (2) comprises the following steps: a. reacting the rare earth upconversion nanoparticle with 3,4-dihydroxyphenylpropionic acid to obtain DHCA-UCNPs; b. reacting DHCA-UCNPs, X-TCPP, ZrOCl2·8H2O, and benzoic acid in a solution to obtain a core-shell structure nanocomposite UMOF(X).
6. The production method according to claim 4 or 5, characterized by, Step (3) comprises the following step: loading a near-infrared dye on the core-shell structure nanocomposite of step (2) by a solvent-assisted method.
7. The production method according to claim 4 or 5, characterized by, Step (4) comprises the following steps: dispersing the UMOF(X) / Y in a solvent, adding an amphiphilic phospholipid polymer, stirring overnight in a dark environment at room temperature, and removing the solvent to obtain the upconversion nanocomposite UMOF(X) / Y-Lipo.
8. Use of the upconversion nanocomposite according to any one of claims 1-3 or prepared by the method according to any one of claims 4-7 in the preparation of a photodynamic bactericidal drug.